2021
DOI: 10.15587/2519-4852.2021.235939
|View full text |Cite
|
Sign up to set email alerts
|

Research in phytochemical composition and hypoglycemic activity screening of the dry extracts from bearberry leaves

Abstract: Diabetes mellitus is a global medical and social issue. In the developed countries of the world, from 5 to 12% of the population are diagnosed with diabetes mellitus and, according to WHO prognosis, the level of this disease may increase to 30-35%. Type 2 diabetes is a disease that progresses over time, but the rational and systematic use of hypoglycemic synthetic drugs and phytopreparations can significantly delay the onset of insulin therapy. A promising source of BAS with a hypoglycemic effect is the raw ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that plants in the Vaccinium genus are promising sources for the creation of hypoglycemic and hypolipidemic agents because of their significant antioxidant activity, namely extracts from bilberry leaves [ 16 ], blueberry leaves [ 17 ] and bearberry leaves [ 18 , 19 ]. Studies have shown that extracts from the leaves of cranberries are also promising when used to correct insulin-resistant conditions [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that plants in the Vaccinium genus are promising sources for the creation of hypoglycemic and hypolipidemic agents because of their significant antioxidant activity, namely extracts from bilberry leaves [ 16 ], blueberry leaves [ 17 ] and bearberry leaves [ 18 , 19 ]. Studies have shown that extracts from the leaves of cranberries are also promising when used to correct insulin-resistant conditions [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of a blueberry-leaves extract with arginine led to the creation of a new remedy with pronounced hypolipidemic and hypoglycemic effects [ 16 ]. The combination of phenylalanine with a bearberry-leaves extract allowed the researchers to obtain a product with anti-inflammatory and pronounced diuretic activity [ 18 , 19 ] and with cysteine—a new one for insulin resistance management [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that plants of the Vaccinium genus are promising sources for the creation of hypoglycemic and hypolipidemic agents, because of their significant antioxidant activity, namely extracts from bilberry leaves [18,19], blueberry leaves [20] and bearberry leaves [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The modification of the blueberry leaves extract with arginine allowed to create a substance with pronounced hypoglycemic and hypolipidemic activities [18]. The modification of the extract of bearberry leaves with phenylalanine allowed to create a substance with a pronounced diuretic and anti-inflammatory effect [21,22] and adding cysteine -a remedy for the management of insulin resistance [28]. All of this indicates the viability of the chosen direction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the extracts obtained from the leaves of Vaccinium genus species are promising for formulating hypoglycemic and hypolipidemic medicines. More specifically, such extracts were obtained, e.g., from bilberry leaves [10,11], highbush blueberry leaves [12], and bearberry leaves [13,14]. Moreover, the extracts of American cranberry leaves were proven to have hepatoprotective effects [8].…”
Section: Introductionmentioning
confidence: 99%